2016
DOI: 10.1159/000453170
|View full text |Cite
|
Sign up to set email alerts
|

RNAi-Mediated Down-Regulation of CD47 Protects against Ischemia/Reperfusion-Induced Myocardial Damage via Activation of eNOS in a Rat Model

Abstract: Key Words CD47 • Ischemia/reperfusion injury • Endothelial nitric oxide synthase • Oxidative stress • RNA interferenceAbstract Background/Aims: Oxidative stress is strongly implicated in the pathogenesis of myocardial damage caused by ischemia reperfusion (I/R). Previous studies have confirmed that cardiac CD47 drives left ventricular heart failure. However, the role for CD47 in myocardial I/R injury (MIRI) has not previously been proposed. This study was designed to investigate whether down-regulation of CD47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…Several physiological mechanisms promote ischemia and lead to hypoxia and hypoperfusion, including atherosclerosis and acute myocardial infarction [10, 11]. The obstruction of arterial blood flow causes hypoxia and leads to dysfunction of the electron transport chain in mitochondria.…”
Section: Mechanism Of Ischemia-reperfusion Injurymentioning
confidence: 99%
“…Several physiological mechanisms promote ischemia and lead to hypoxia and hypoperfusion, including atherosclerosis and acute myocardial infarction [10, 11]. The obstruction of arterial blood flow causes hypoxia and leads to dysfunction of the electron transport chain in mitochondria.…”
Section: Mechanism Of Ischemia-reperfusion Injurymentioning
confidence: 99%
“…However, restoration of the blood flow can induce even worse microstructural destruction, termed myocardial ischemia/reperfusion injury (MIRI), which lessens the beneficial effect of reperfusion therapy [1]. Recently, a series of in vitro and in vivo studies have demonstrated that innate inflammation, apoptosis, autophagy, platelet activation, and oxidative stress contribute to MIRI [2][3][4][5][6]. However, there is no effective strategy for limiting or preventing MIRI, so a new molecular therapeutic target is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The activated Akt pathway can regulate cell survival through phosphorylation of a variety of downstream targets, such as pro-apoptotic protein, transcription factors and endothelial nitric oxide synthase (eNOS) [7-9]. The activation of the PI3K/Akt pathway protects the brain from cerebral I/R injury by preventing neuronal apoptosis [10].…”
Section: Introductionmentioning
confidence: 99%